Ekspresi Rekombinan Gen Protein Selubung Pepper vein yellows virus - Rita Kurnia Apindiati; Gede Suastika; Kikin Hamzah Mutaqin (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2015)
Pepper vein yellows virus (PeVYV) isolate from Bali have been identified from pepper plants with chlorosis symptoms. Specific antiserum of PeVYV had not available yet commercially. One of the advance techniques in providing a source of abundant antigen for antiserum production is through molecular approach by overexpressed the coat protein gene in suitable bacterial expression system. PeVYV coat protein gene of 650 bp in size was amplified using specific primers, then was cloned into pQE30 expression vector and was over expressed in E. coli strain M15 [pREP4]. SDS-PAGE analysis showed that the recombinant coat protein gene of PeVYV was successfully expressed protein band with size of 25 kDa at 6 hours after induction by 0.5 mM IPTG on 37 °C.